Assessment of peri- and postoperative complications and Karnofsky-performance status in head and neck cancer patients after radiation or chemoradiation that underwent surgery with regional or free-flap reconstruction for salvage, palliation, or to improve function - Simon, Christian; Bulut, Cem; Federspil, Philippe A.; Münter, Marc; Lindel, Katja; Bergmann, Zazie; Sertel, Serkan; Leitzbach, Sarah; Plinkert, Peter K. (Radiation oncology, 2011)
Surgery after (chemo)radiation (RCTX/RTX) is felt to be plagued with a high incidence of wound healing complications reported to be as high as 70%. The additional use of vascularized flaps may help to decrease this high rate of complications. Therefore, we examined within a retrospective single-institutional study the peri--and postoperative complications in patients who underwent surgery for salvage, palliation or functional rehabilitation after (chemo)radiation with regional and free flaps. As a second study end point the Karnofsky performance status (KPS) was determined preoperatively and 3 months postoperatively to assess the impact of such extensive procedures on the overall performance status of this heavily pretreated patient population.
Gesehen am 14.10.2022